2017
DOI: 10.1126/scisignal.aai9248
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial homeostasis in adipose tissue remodeling

Abstract: Mitochondrial homeostasis is regulated by a balance between mitochondrial biogenesis and degradation. Emerging evidence suggests that mitophagy, a selective form of autophagy that degrades mitochondria, plays a key role in the physiology and pathophysiology of mitochondria-enriched cells, such as brown and beige adipocytes. This review discusses findings regarding the roles of autophagy and mitophagy in cellular development, maintenance, and functions of metabolic organs, including adipose tissue, liver, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 107 publications
(113 reference statements)
2
78
0
Order By: Relevance
“…For instance, the transforming growth factor β (TGF β) and Notch signaling pathways were shown to react as negative regulators of thermogenesis in obese mice [34]. Furthermore, autophagy was found to dysregulate beige adipogenesis, as inhibiting autophagy through deletion of Atg7 in adipocytes led to increased beige adipocyte differentiation in DIO mice [35, 36]. Our group also has observed that autophagy profoundly contributes to LPS-induced beige fat inhibition [13].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the transforming growth factor β (TGF β) and Notch signaling pathways were shown to react as negative regulators of thermogenesis in obese mice [34]. Furthermore, autophagy was found to dysregulate beige adipogenesis, as inhibiting autophagy through deletion of Atg7 in adipocytes led to increased beige adipocyte differentiation in DIO mice [35, 36]. Our group also has observed that autophagy profoundly contributes to LPS-induced beige fat inhibition [13].…”
Section: Discussionmentioning
confidence: 99%
“…The control of cellular mitochondrial content and oxidative capacity is important for cellular and organismal energy homeostasis 25 . For example, brown and beige adipocytes generate new mitochondria and increase their oxidative and thermogenic capacity in response to norepinephrine (NE), which is secreted locally when the organism senses a cold environment 26 .…”
Section: Bench Validation Use Case 3: the Murine Err Ppargc And Adipmentioning
confidence: 99%
“…For example, obesity impairs MT biogenesis. [19][20][21] MT dysfunction has been also implicated in the development of insulin resistance. [22][23][24] Thus, our study prioritized obesity and insulin resistance pathways to CVD.…”
Section: Introductionmentioning
confidence: 99%